Candidemia and invasive candidiasis: pathogenesis, molecular epidemiology, and predictors of outcome. A population-based study - Lena Rós Ásmundsdóttir 1976- (2008)
The incidence of serious fungal infections has increased substantially in the past decades, incident to increased prevalence of susceptible hosts. Candidemia, in particular, is associated with high morbidity and mortality. This thesis outlines results from a nationwide study, conducted in Iceland from 1980 to 2006, of the incidence of candidemia. In addition, antifungal susceptibility of the pathogens was studied, as well as national consumption of antifungal agents. The clinical characteristics of candidemic patients (n=165; 172 episodes) from 1980 through 1999 are described, as well as predisposing conditions and their association with outcome. Furthermore, we studied the genetic relatedness of all available Candida bloodstream isolates (BSIs) in the country during a 15-year period. Finally, the virulence of Candida albicans and Candida dubliniensis were compared in a murine model of bloodstream infections. The annual incidence of candidemia in Iceland increased from 1.4 cases/100,000 inhabitants/year during 1980-1984 to 5.3 cases/100,000 inhabitants/year during 2000-2006 (p<0.001), with the greatest increase in incidence occurring among infants <1 year of age and the elderly (age, >60 years). C. albicans was the predominant species responsible (61.6%). The national import of fluconazole increased approximately 5.5-fold from 1991 through 2006, but increased resistance to this agent was not observed. Most cases occurred in intensive care units (35.8%) and surgical wards (30.1%). In multivariate analysis, prompt removal of central venous catheters (odds ratio [OR], for death, 0.22) and septic shock (OR for death, 8.01) were the strongest independent predictors of outcome. PCR fingerprinting of Candida BSIs (n=219) from 94.4% of cases during 1991-2006 revealed temporo-spatial associations between 18.7-39.9% of all infections, suggestive of nosocomial clustering. When the virulence of C. albicans and C. dubliniensis was compared in a murine model, similar 7-day mortality was observed, with greater strain ...